The bottom billion : why the poorest countries are failing and what can be done about it - Collier, Paul. (Oxford ; New York : Oxford University Press, 2007)
Global poverty, economist Collier points out, is actually falling quite rapidly for about 80% of the world. The real crisis lies in a group of about 50 failing states, the bottom billion, whose problems defy traditional approaches to alleviating poverty. Here, Collier contends that these fifty failed states pose the central challenge of the developing world in the twenty-first century. This group of small nations, largely unnoticed by the industrialized West, are dropping further and further behind the majority of the world's people, often falling into an absolute decline in living standards. A struggle rages within each of these nation between reformers and corrupt leaders--and the corrupt are winning. Collier analyzes the causes of failure, and offers a bold new plan.--From publisher description.
Includes index.
Bibliography: p. 193-195.
Keywords: Poverty -- Developing countries